2020
DOI: 10.3390/nu12030708
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of DHA Supplementation on Cognition in Patients with Bipolar Disorder: An Exploratory Randomized Control Trial

Abstract: Bipolar disorder (BD) is a severe mental disorder with a wide range of cognitive deficits, both in the euthymic and acute phase of the disease. Interestingly, in recent years, there has been a growing interest in investigating the impact of ω-3 polyunsaturated fatty acids on cognition in BD. In this context, the aim of this study is to evaluate the effect of docosahexaenoic acid (C22:6 ω-3, DHA) supplementation on cognitive performances in euthymic BD patients. This is an exploratory, single-centre, double-bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…When intervention trials on parameters of cognition published up to 2015 were broken down according to dose of DHA used, it became apparent that trials using more than 600 mg DHA per day had positive results in terms of aspects of memory, executive function, or aspects of learning, while those using lower doses largely had neutral results [ 12 ]. However, more recently, both neutral and positive results were published with doses >600 mg DHA per day [ 119 , 120 , 121 , 122 , 123 , 124 , 125 ]. One trial found the improvement in executive function and verbal fluency to correlate with the increase of EPA in red cells, as well as improvements in pertinent brain structures [ 126 ].…”
Section: Brain Health In Adulthood–cognition and Dementiamentioning
confidence: 99%
“…When intervention trials on parameters of cognition published up to 2015 were broken down according to dose of DHA used, it became apparent that trials using more than 600 mg DHA per day had positive results in terms of aspects of memory, executive function, or aspects of learning, while those using lower doses largely had neutral results [ 12 ]. However, more recently, both neutral and positive results were published with doses >600 mg DHA per day [ 119 , 120 , 121 , 122 , 123 , 124 , 125 ]. One trial found the improvement in executive function and verbal fluency to correlate with the increase of EPA in red cells, as well as improvements in pertinent brain structures [ 126 ].…”
Section: Brain Health In Adulthood–cognition and Dementiamentioning
confidence: 99%
“…But combined DHA and EPA supplementation for 6 weeks improved mania and depression among juvenile patients [233][234][235]. However, recent RCT found DHA has no role in improving the symptoms of bipolar disorder [15].…”
Section: Dha Deficiency and Human Brain Functionmentioning
confidence: 98%
“…Intake of DHA improves attention deficit hyperactivity disorder (ADHD), bipolar disorder, schizophrenia, impulsive behavior, and other brain disorders [15,115,117].…”
Section: Structural and Functional Roles Of Dha In The Human Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, this Research Topic corroborated the fact that nowadays, we need further research on the genetic, neurobiological, and cognitive bases of major psychiatric disorders in order to better delineate different domains charactering commonalities and dissimilarities across different spectrum and continuum diagnostic prototypes ( 3 ). This will ultimately help us to have an evolute idea of how human brain impairments affect neuropsychological functions, behavioral characteristics, general functioning, outcome, and disease trajectory of our patients ( 4 ). We finally, last but not least, thank the estimated authors who contributed to the issue to allow us to have the privilege to coordinate and guest edit such a prestigious issue.…”
mentioning
confidence: 99%